Attitudes and Behaviour Community Toward Using Vitamin Supplements to Improve the Immunity during the COVID-19 Pandemic - Wiyati, Tuti; Maifitrianti, Maifitrianti; Zaid, Liesca Tria Novalita; Bahiah, Faridatul (Indonesian Journal of Clinical Pharmacy, 2023)
During the COVID-19 pandemic, the consumption of vitamin supplements has become a new habit. As a result of the epidemic, people's attitudes and behaviours had altered, particularly when it came to consuming vitamin supplements to boost immunity or maintain health. The aim of this study was to analyze the correlation between the attitude and behaviour of the community toward vitamin supplements during the COVID-19 pandemic. A cross-sectional study was conducted in two cities in Indonesia, Jakarta and Pandeglang Banten, in August-October 2021. Each subject filled out an attitude and a behavioural questionnaire, both of which were made by researchers based on many references. All data collected by google form software analyzed the Socioeconomi characteristics by chi Square test, while the correlation of attitude and behaviour tested by Spearman rho test. The characteristics of Socioeconomi such as education, consumption of vitamin supplements during the COVID-19 period, and people's residence were correlated significantly with attitude and behaviour (P<0.005). there was a significant correlation between attitude and behaviour in using vitamin supplements to increase immunity during the COVID-19 pandemic (P=0.001, correlation coef=0.465). The correlation was moderate strength with a positive path correlation. It means that the more support an attitude, the more behaviour will increase to use vitamin supplements during COVID-19 pandemic.